Pembuatan HRM Apps Sebagai ERP Berbasis Mobile Melalui Rest API - Nur Cahyo Wibowo; Lavenia, Nur Lickha (EDUPEDIA Publisher, 2023)
It is undeniable that information technology is one of the main drivers of innovation in a business by enabling new ways to create and capture value, mechanisms for exchange of values and transactions, and the formation of a more adaptive organizational structure. One of the information technologies adopted and implemented by the company in optimizing the management of all of its resources is the ERP system. In this study, the ERP system implementation process was examined using odoo software at PT. XYZ which is an ERP provider that has 1750+ clients in several city companies in Indonesia. One of the implemented modules is the human resource management module which will accommodate the human resource management process in the company. In this module there are several sub-modules such as employees, leave/leave, nursing, contracts, and attendance. In implementing this system, using the rest API to connect applications with the company's back-office system.